MEDIA GAMBAR BERANTAI UNTUK MENINGKATKAN KETERAMPILAN MENULIS FABEL SISWA FASE D - Taqi Kirey Devana, Marsya; Juanda (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2023)
This study aims to improve the learning outcomes of grade VII students at SMPK YBPK Wonorejo, on fable writing material using chain image media. The reason is, student learning motivation is very low because the material is considered saturated, thus reducing student interest in learning. In addition, it is also influenced by teachers who are less innovative in using image media and make students less active in class. In fact, with image media is believed to increase students' interest in learning. This research is a classroom action research that uses a qualitative approach. The place where this research was carried out was at SMPK YBPK Wonorejo, with the research subjects of grade VII students totaling 13 students. Data collection techniques include observation, interview, test, and document analysis techniques. The collected data is then processed so that the conclusions can be known in each cycle. The stages of each cycle include planning, action, observation, and reflection. The results of the recapitulation in cycle I showed that 8 students (62%) successfully completed writing fables, and in cycle II there was a significant increase in which 13 students (100%) successfully completed writing fables. So, chain image media is able to increase learning motivation and learning outcomes of phase D students at SMPK YBPK Wonorejo.